Meningkatkan Hasil Belajar IPS Siswa Melalui Penggunaan Media Gambar - yenimar yenimar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
In fact, learning process in some schools still run with teacher centered condition. It caused students feeling bored and not participate actively. To create the active and enjoy learning process, one of solutions is by using media of picture. This study was conducted at 4th grade of SDN 26 Sungai Limau Kabupaten Padang Pariaman.This study is a classroom action research with two cycles. Each of cycle consists of two meetings. Procedure of this research includes four steps, i.e. planning, implementation, observation, and reflection. This study aimed to improve students’ learning achievement in social subject by implementing media of picture.Percentage of students’ learning achievement in cycle I is 67% and 81% for cycle II. Findings and analysis of data show that media of picture can improve students’ learning achievement in social subject.